Model Cooperative Learning Tipe Student Teams Achievement Divisions (STAD): Dampaknya terhadap Motivasi Belajar Siswa - Erly, Erly (Indonesian Journal of Science and Mathematics Education, 2020)
High motivation to learn will encourage and move students to always move and achieve the best results. The purpose of this study was to see an increase in student motivation through the cooperative learning model Student Teams Achievement Divisions (STAD) type. The method used in this study is the Classroom Action Research (CAR) method. The population in this study were all students of class XII Science in SMA 2 Bandar Lampung. Sampling is done by simple random sampling technique. The sample in this study was 38 people. The analysis technique uses an independent sample t-test. The results showed that the implementation of the Student Teams Achievement Division (STAD) type of cooperative learning model on the principles of redox and electrochemical reactions were used to test student learning. The results of this study also discussed increasing students' motivation to learn including motivation to cooperate with each other, discuss, help each other, and ask questions